2019
DOI: 10.1186/s12906-019-2491-y
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese medicine use is associated with lower end-stage renal disease and mortality rates among patients with diabetic nephropathy: a population-based cohort study

Abstract: Background Diabetic nephropathy (DN) is a common complication of diabetes mellitus (DM) that imposes an enormous burden on the healthcare system. Although some studies show that traditional Chinese medicine (TCM) treatments confer a protective effect on DN, the long-term impact remains unclear. This study aims to examine end-stage renal disease (ESRD) and mortality rates among TCM users with DN. Methods A total of 125,490 patients with incident DN patients from 2004 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 51 publications
2
45
1
Order By: Relevance
“…f. extracts [45]. Besides, a population-based cohort study by Chen et al revealed that Chinese herbal remedies lowered ERSD and mortality rates among DKD patients [46]. Recent studies on DKD suggest certain Chinese herbal agents exert autophagy-inducing functions [18], implying autophagy activation may act as a potential target for its renoprotective action in DKD therapy; meanwhile, the mechanisms of how herbal medicine exerts renal benefits on DKD are addressed through different pathways related to autophagy mainly involving mTOR, AMPK, and Sirt1 (Table 1).…”
Section: Mechanisms Of Chinese Herbal Medicine Treating Dkd Via Acmentioning
confidence: 99%
“…f. extracts [45]. Besides, a population-based cohort study by Chen et al revealed that Chinese herbal remedies lowered ERSD and mortality rates among DKD patients [46]. Recent studies on DKD suggest certain Chinese herbal agents exert autophagy-inducing functions [18], implying autophagy activation may act as a potential target for its renoprotective action in DKD therapy; meanwhile, the mechanisms of how herbal medicine exerts renal benefits on DKD are addressed through different pathways related to autophagy mainly involving mTOR, AMPK, and Sirt1 (Table 1).…”
Section: Mechanisms Of Chinese Herbal Medicine Treating Dkd Via Acmentioning
confidence: 99%
“…Additionally, a previous study in a Taiwanese cohort revealed that the 8-year cumulative incidence in the ESKD rate among individuals with diabetic nephropathy was 14.5% (95% CI, 13.9-15.0) for people using traditional Chinese medicine and 16.6% (95% CI, 16.0-17.2) for people who did not use traditional Chinese medicine . 12 A 2017 study 13 found that in a Taiwanese population, a family history of ESKD was a risk factor associated with developing ESKD, suggesting a moderate level of heritability in the Taiwanese population. In addition to well-known risk factors of ESKD, such as diabetes, hypertension, dyslipidemia, and advanced age, infection-related kidney disease has become a subject of recent research.…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin, mainly derived from dried rhizome of Curcuma longa L , possesses multiple pharmacological abilities, including anticancer, anti-inflammatory, antioxidation, antifibrotic, anti-arthritis ( Hatcher et al, 2008 ; Azhdari et al, 2019 ), as well as a neuroprotective effect ( Sun et al, 2017 ). Both rhein and curcumin have antifibrotic activity and have showed good efficacy to prevent the progress of renal fibrosis ( Kuwabara et al, 2006 ; He et al, 2011 ; Soetikno et al, 2013 ; Zhou et al, 2014 ; Ho et al, 2016 ; Hu et al, 2016 ; Zhang et al, 2016 ; Chen et al, 2019b ). Therefore, further investigation of the antifibrosis effect of rhein and curcumin was of great significance for the development of new antifibrosis drugs.…”
Section: Introductionmentioning
confidence: 99%